Lifestyle and Atrial Fibrillation: The Role of Obesity, Exercise, and Weight Loss in Risk Reduction and Rhythm Management - Szymon Pucyło; Martyna Skweres (Journal of Education, Health and Sport)
Introduction and puropse. Atrial fibrillation (AF) is the most common sustained arrhythmia worldwide, closely associated with rising obesity rates and sedentary lifestyles. This review evaluates the evidence linking obesity, physical activity, and weight reduction with AF development, progression, and management.